Design and testing of the filling-plate of inner-filling positive pressure high-speed seed-metering device for maize. (April 2023) - Du, Xin; Liu, Cailing
Abstract : To overcome the problem for high-speed maize seeding of increasing seed leakage caused by insufficient seed filling force, a metering device using internal air pressure was designed. Seed was filled into the seeding disc using a combination of internal filling and positive air pressure using a brush belt to guide the seed synchronously after clearing. The design of the structure and dimensional parameters of the inner filling disc were optimised with the "lying flat" position was determined from the posture of the seeds pressing against the hole surface when filling a single seed. The angle of the tapered hole was calculated to be >0.9018 rad. A force analysis of the seed-filling process was performed, and a model developed for variation in airflow with filling angle and cone angle of the inner filling disc. A single-factor simulation test using discrete element method with computational fluid dynamics modelling was performed. A quadratic model was fitted for leakage rate. Predicted values of qualified rate, multiple rate, and leakage rate were 97.16%, 1.75%, and 1.09% for hole diameter, taper opening, and cone angle of 18 mm, 1.1825 rad, and 0.7828 rad, respectively. Errors between the predicted and measured values were small. Optimal parameters for an operating speed of 8–16 km h −1 were a qualified rate of the seed rower >90%, multiple rate <2.4%, and a leakage rate <8.0%, meeting the agronomic requirements for maize precision sowing. Highlights: Novel high-speed precision seed-metering device for maize was designed. Increased seed filling force and reduced non-essential air loss were obtained. Posture of a single seed pressed on the shaped hole determined as "lying flat". Structural and dimensional parameters of shaped holes designed. Performance optimised using DEM-CFD modelling.